Seasonal water-heat-salt dynamics in coastal salinized fields: impacts on cotton photosynthesis and yield - Guoyi Feng; Guoyi Feng; Qian Zhang; Qian Zhang; Yan Wang; Yan Wang; Ming Dong; Ming Dong; Shulin Wang; Shulin Wang; Zhe Wu; Hong Qi; et al. (Frontiers in Plant Science, 2025)
IntroductionSoil moisture, temperature, and salinity critically constrain cotton production in saline soils. Understanding how cotton photosynthetic characteristics and yield respond to seasonal water-heat-salt dynamics is essential for improving management practices in these challenging environments.MethodsA two-year field study (2015–2016) was conducted comparing cotton growth, photosynthetic characteristics, and yield in mildly, moderately, and severely salinized fields. Seasonal soil water-salt dynamics in the 0–200 cm layer were monitored.Resultsseasonal rainfall and temperature fluctuations significantly influenced soil water-salt dynamics in the 0-140 cm layer. During spring (April-May), drought maintained soil salinity above 3 g/kg, while low temperatures delayed cotton germination by over a day. In rainy season (July-August), rainfall leached salts from topsoil (0-40 cm), reducing salinity to below 5 g/kg and alleviating salt stress. Mildly saline fields exhibited superior photosynthetic performance, with leaf area index, chlorophyll content, and canopy photosynthetic rate being 1.2–1.5 times higher than in moderate/severe fields. These fields also showed extended "source-sink" organ development periods (16–28 days for "source," 4–24 days for "sink") and 13.8%–18.8% greater boll weight, ultimately achieving a seed cotton yield of 3,303 kg/ha—34.3%–120.7% higher than yields from moderate/severe fields.DiscussionOur results indicate that excessive soil salinity primarily impairs photosynthetic capacity and disrupts photosynthate allocation to bolls. Strategic interventions like drip irrigation could mitigate salt stress while improving photosynthetic efficiency and yield, providing practical solutions for cotton cultivation in saline fields.